Defective function of lymphokine-activated killer cells and natural killer cells in patients with hepatocellular carcinoma - Saibara, T; Onishi, S; Sakaeda, H; Yamamoto, Y (Hepatology (Baltimore, Md.), 1989)
Lymphokine-activated killer activity and natural killer activity in hepatocellular carcinoma patients were assessed. Maximum lymphokine-activated killer activity was induced at 3 to 5 days of incubation, and lymphokine-activated killer activity tended to increase in a manner dose dependent of recombinant interleukin-2. However, the maximum increase of lymphokine-activated killer activity in hepatocellular carcinoma was not as high as that of normal subjects or liver cirrhosis patients. Lymphokine-activated killer activity was impaired in hepatocellular carcinoma as compared to that in normal subjects. Hepatocellular carcinoma seemed to consist of two groups: i.e. a high-lymphokine-activated killer activity group and a low-lymphokine-activated killer activity group. Reduction of natural killer activity was also observed in hepatocellular carcinoma as compared with that in normal subjects and patients with liver cirrhosis. No correlation could be demonstrated between natural killer activity and lymphokine-activated killer activity in normal subjects, liver cirrhosis patients and hepatocellular carcinoma patients. With regard to the presence of HBsAg or alpha-fetoprotein concentration in the sera, there was no significant difference in natural killer and lymphokine-activated killer activity in hepatocellular carcinoma patients. Patients with a small mass lesion showed a low lymphokine-activated killer activity, and depressed lymphokine-activated killer activity was not necessarily related to tumor size. In comparison with the high-lymphokine-activated killer group, the low-lymphokine-activated killer group showed a significant decrease in gamma-interferon production and a preserved function of indocyanine green clearance.